STEM CELLS AND ITS CLINICAL APPLICATIONS – AN OVERVIEW - M. RAJESH; A. S. WILLIAM ARPUTHA SUNDAR; N. NARAYANAN; H.NELLIAH (International Journal of Pharma and Bio Sciences, 2010)
Stem cells are unspecialized cells, capable of dividing and renewing themselves for long periods, can give rise to specialized cells. Stem cell technology is a novel approach, which provides the possibility of cell-based therapies to treat diseases, which are often referred to as regenerative or reparative medicine. The present article gives a broad overview about the stem cells, their importance, types, and their use in research and in treating disease. Various types of stem cells available such as Embryonic Stem cells taken from human embryos, Foetal stem cells from aborted fetal tissue, Umbilical stem cells from umbilical cord after birth, Adult stem cells from Adult tissue, stem cells from bone marrow and Stem cells from fat sucked out of liposuction patients. The primer includes information mainly about stem cells derived from the embryo & adults.